Implementation of the Bandongan Learning Method at Jamsaren Islamic Boarding School, Surakarta - Khairunnisa, Nabila; Istanto (Tadrib: Jurnal Pendidikan Agama Islam, 2025)
Islamic boarding school education in Indonesia plays a crucial role in shaping the religious values and character of students. One of the traditional teaching methods still in use today is the bandongan method, which relies on the oral teaching of yellow books (kitab kuning) by kiai to santri (students). Although it has been practiced for centuries, the relevance of this method in the context of modern education, which demands interactive and technology-based learning, remains a topic that warrants further study. This research aims to analyze the implementation of the bandongan method at Jamsaren Islamic Boarding School, Surakarta, by exploring its implementation, identifying factors that influence it, and providing a comprehensive overview of the learning conditions at the boarding school. This research employs a qualitative approach, utilizing field research methods and a case study design. Research subjects include ustadz (teachers) and santri, with data collection techniques through in-depth interviews, direct observation, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The research results show that the bandongan method remains effective in conveying religious teachings authoritatively and preserving the scholarly tradition of pesantren, despite limited interaction between teachers and santri. To address 21st-century educational challenges, pesantren are advised to conduct learning innovations by integrating technology and more participatory approaches. This research is expected to make a significant contribution to the development of traditional learning methods that remain adaptable and relevant to contemporary needs